Golden Ratio and Fibonacci Quadratic Equation in Business and Finance - Kumar, Nand Kishor; Shah, Raj Kumar; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2025)
The Golden Ratio and Fibonacci quadratic equation provide powerful insights into financial decision-making. From stock market analysis to business growth strategies, these mathematical principles offer practical applications in the financial world. By leveraging it, finance and investors can enhance their forecasting, optimize risk assessment, and improve financial outcomes. The existence of this Fibonacci sequence is not coincidental since it has been properly developed and maintained. There are more possibilities to study the mathematical properties of the Fibonacci numbers in the contemporary mathematics curriculum. Research into Fibonacci numbers facilitates the investigation of the existence of the Fibonacci sequence in God's beautiful essence. In short, God's dominance over humans is illustrated by the Fibonacci numbers and sequence.